2012
DOI: 10.1128/mcb.06388-11
|View full text |Cite
|
Sign up to set email alerts
|

Sam50 Functions in Mitochondrial Intermembrane Space Bridging and Biogenesis of Respiratory Complexes

Abstract: f Mitochondria possess an outer membrane (OMM) and an inner membrane (IMM), which folds into invaginations called cristae. Lipid composition, membrane potential, and proteins in the IMM influence organization of cristae. Here we show an essential role of the OMM protein Sam50 in the maintenance of the structure of cristae. Sam50 is a part of the sorting and assembly machinery (SAM) necessary for the assembly of ␤-barrel proteins in the OMM. We provide evidence that the SAM components exist in a large protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
249
0
21

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(297 citation statements)
references
References 52 publications
18
249
0
21
Order By: Relevance
“…In human cells, mitofilin was found to interact with the sorting and assembly machinery of the outer membrane (SAM complex) that has a central role in the biogenesis of outer membrane proteins ( Figure 2B) (Xie et al , 2007 ;Darshi et al , 2011 ;Alkhaja et al , 2012 ;Ott et al , 2012 ). In yeast, interactions of mitofilincontaining protein complexes of the inner membrane with the SAM complex, the TOM complex, porin channels and Ugo1 have been reported (Figure 2A) (Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;K ö rner et al, 2012 ;Zerbes et al , 2012 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 98%
See 4 more Smart Citations
“…In human cells, mitofilin was found to interact with the sorting and assembly machinery of the outer membrane (SAM complex) that has a central role in the biogenesis of outer membrane proteins ( Figure 2B) (Xie et al , 2007 ;Darshi et al , 2011 ;Alkhaja et al , 2012 ;Ott et al , 2012 ). In yeast, interactions of mitofilincontaining protein complexes of the inner membrane with the SAM complex, the TOM complex, porin channels and Ugo1 have been reported (Figure 2A) (Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;K ö rner et al, 2012 ;Zerbes et al , 2012 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 98%
“…The possibility of such an overlapping localization has been repeatedly addressed, although never comprehensively clarified (van der Klei et al , 1994 ;Perkins et al , 1997 ;Reichert and Neupert , 2002 ;Harner et al , 2011 ;K ö rner et al, 2012 ). Some studies have suggested that the integrity of crista junctions may depend on their anchoring to the outer mitochondrial membrane via mitofilin-containing contact sites (Harner et al , 2011 ;K ö rner et al, 2012 ;Ott et al , 2012 ). Along the same lines, downregulation of the SAM complex, one of the outer membrane interaction partners of mitofilin, was found to result in alterations of mitochondrial ultrastructure in human cultured cells and yeast ( K ö rner et al, 2012 ;Ott et al , 2012 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%
See 3 more Smart Citations